Effectiveness of Ficus benjamina "Vaditi" and Artocarpus treculianus Elm. "Tipuho" Sap Extracts as Non-Chemical Rodent Trap - William Jo Se Billote; Paul Alcantara; Dean Eduard Cadid; Keenen Ivory Delos Reyes; Aira Marie Entela; Maria Angelica Gabotero; Ryan Ponce (Philippine Association of Institutions for Research, Inc., 2020)
Pests are organisms that can cause economic damage or become threats to the health of humans and domestic animals. Rodents are pests and are considered to be essential reservoirs of numerous diseases that infect humans, domestic animals, and other wildlife species. Because of the threats, they have on humans and the environment, there is a need to employ an effective method to control rodent infestations that are inexpensive and non-chemical. The purpose of this study is to create a non-chemical and eco-friendly rodent trap from the sap extracts of Ficus benjamina and Artocarpus trecalianus Elm. Two different samples of rodent traps were prepared. The samples were tested in an area infested by rats within 24 hours. The sample sap extracts in both the controlled and experimental groups were observed within the first 0 to 8 hours and within the remaining time (9 to 24 hours). This procedure was replicated five times in both groups. Descriptive statistics and t-Test were then used to analyze and compare the data. Based on the study, the non-chemical rodent trap, mainly the decocted sap extracts from Ficus benjamina and Artocarpus treculianus Elm. mixed with pure honey extract were found to be a capable alternative rodent trap.